Inhibition of Ovulation in Ewes after chloropramazine (largactil) Administration - ΤΣΑΜΗΣ K.; ΛΟΥΚΕΡΗΣ Α. (Journal of the Hellenic Veterinary Medical Society, 2019)
An experimental research was carried out in June 1976 on ewes of the High Argicultural College of Athens, to find out the efficacy of ehloropromazine administration in the inhibition of ewes ovulation. 8 ewes were used for the expriment divided in 2 same number groups. Sponges impregnated with 50 mg M.A.P. (Vet. cycle) were put in the vagina of all ewes. 12 days after placing the sponges 500 i.u. Pregnant mare serum gonadotrophin (P M S G) were injected to each ewe and two days later the sponges were removed. The day of sponges removal as well as the next two days 50, 40 and 25 mg ehloropromazine were injected respectively to each ewe of the experimental group. 6 days after Ρ M S G treatment the were slaughtered. The percetage of ovulation inhibition in the ewes treated by ehloropromazine was 75% with fuliy mature fol ides. 100% of the controls had corpus luteum.